2018
DOI: 10.1016/j.jwpe.2018.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Removal of total organic carbon from peat solution by hybrid method—Electrocoagulation combined with adsorption

Abstract: Humic substances end up in water from the drainage basin causing eutrophication and the spread of algae.These natural organic substances have an influence on the physical, chemical and biological properties of the water system. Adsorption and electrocoagulation (EC) are commonly used purification methods in the water and wastewater treatment. Both methods are used by themselves for removing a wide range of impurities. In this research, the novelty was to study the effect of combined activated carbon (AC) adsor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 36 publications
0
7
0
2
Order By: Relevance
“…Electrocoagulation method (EC) has recently brought a big deal of attention as an effective method to remove microorganisms from wastewater and water because of its simplicity, selectivity, and relatively low operating cost [17][18][19]. Additionally, the EC technology does not need chemical additives to achieve the treatment process, and it could be easily automated and integrated with other treatment units [20][21][22]. Furthermore, EC method significantly minimises the volume of the generated solid waste (sludge) that requires high treatment cost [23,24], which in turn significantly minimises the operational cost of the EC method.…”
Section: Introductionmentioning
confidence: 99%
“…Electrocoagulation method (EC) has recently brought a big deal of attention as an effective method to remove microorganisms from wastewater and water because of its simplicity, selectivity, and relatively low operating cost [17][18][19]. Additionally, the EC technology does not need chemical additives to achieve the treatment process, and it could be easily automated and integrated with other treatment units [20][21][22]. Furthermore, EC method significantly minimises the volume of the generated solid waste (sludge) that requires high treatment cost [23,24], which in turn significantly minimises the operational cost of the EC method.…”
Section: Introductionmentioning
confidence: 99%
“…Pada kondisi tegangan 30 V, waktu adsorpsi 45 menit, serta dosis adsorben 5 g/L. Kombinasi metode elektrokoagulasi dan absorpsi dapat meningkatkan efisiensi penyisihan Pb(II) hingga 95% jika dibandingan dengan mengunakan satu metode guna menurunkan kandungan polutan pada air limbah (Myllymäki, 2018).…”
Section: Gambar 2 Spektra Ftir Karbon Aktif Sebelum Dan Setelah Aktiunclassified
“…Iron salts were hydrolyzed in water to produce insoluble precipitates, which then adsorb on the surface of the particles, destabilizing their charge. Because the particles have identical electric charges, which are usually negative, they have repulsive interactions 25 , found that the hydrolyzed products had a positive electric charge. On the surface of the cathode, electrolytically created gases, primarily hydrogen, are produced.…”
Section: Introductionmentioning
confidence: 99%